The Role of Cell Organelles in Rheumatoid Arthritis with Focus on Exosomes - Zahra Payandeh (BMC, 2021)
Abstract Auto-immune diseases involved at least 25% of the population in wealthy countries. Several factors including genetic, epigenetic, and environmental elements are implicated in development of Rheumatoid Arthritis as an autoimmune disease. Autoantibodies cause synovial inflammation and arthritis, if left untreated or being under continual external stimulation, could result in chronic inflammation, joint injury, and disability. T- and B-cells, signaling molecules, proinflammatory mediators, and synovium-specific targets are among the new therapeutic targets. Exosomes could be employed as therapeutic vectors in the treatment of autoimmune diseases. Herein, the role of cell organelle particularly exosomes in Rheumatoid Arthritis had discussed and some therapeutic applications of exosome highlighted.